A novel scheme for simulating the effect of microstructure surface roughness on the heat transfer characteristics of subcooled flow boiling - Hasan Alimoradi (Case Studies in Thermal Engineering, 2021)
In this study, the RPI wall boiling model is developed to investigate the surface roughness effect in the subcooled flow boiling. The surface roughness is simulated by two different schemes. A novel scheme for studying the effect of microstructure surface roughness on subcooled flow boiling is developed. The results of this newly developed scheme are compared with the traditional method and a smooth surface. A randomly distributed roughness is generated and used to present Direct Roughness Simulation. The turbulence stresses are simulated by using the k-ε model. The results of both the Surface Roughness Model and the Direct Roughness Simulation method are compared with those of the smooth surface. The surface roughness model changes the wall function near the wall while Direct Roughness Simulation creates randomly distributed cavities of the wall. Results show that the wall surface temperature decreases, and the average vapor volume fraction and heat transfer coefficient are increased by considering the microstructure surface roughness. The effects of different operating conditions such as pressure, heat flux, mass flux, and subcooled temperature on the characteristics of heat transfer in subcooled flow boiling are studied by considering microstructure surface roughness and smooth surface.